2011
DOI: 10.1111/j.1753-4887.2011.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Human gut microbiota and its relationship to health and disease

Abstract: Probiotics are live microorganisms that confer a health benefit on the host when administered in appropriate amounts. Over 700 randomized, controlled, human studies have been conducted with probiotics thus far, with the results providing strong support for the use of probiotics in the clinical prevention or treatment of gastrointestinal tract disorders and metabolic syndrome. The present review is based on webinar presentations that were developed by the American Gastroenterological Association (AGA) in partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(141 citation statements)
references
References 89 publications
0
137
0
4
Order By: Relevance
“…ncreasing attention is currently aimed at understanding the molecular basis by which probiotic bacteria, mainly belonging to the Bifidobacterium and Lactobacillus genera, confer their welldocumented positive health effects (37,53). Utilization of oligosaccharides, not otherwise digestible by human enzymes, has been recognized as an important attribute of probiotics (5,15,28,37).…”
mentioning
confidence: 99%
“…ncreasing attention is currently aimed at understanding the molecular basis by which probiotic bacteria, mainly belonging to the Bifidobacterium and Lactobacillus genera, confer their welldocumented positive health effects (37,53). Utilization of oligosaccharides, not otherwise digestible by human enzymes, has been recognized as an important attribute of probiotics (5,15,28,37).…”
mentioning
confidence: 99%
“…Insulin resistance plays a decisive role in hepatic steatosis, which is closely associated with obesity [26]. Our results from histological analysis demonstrated that a prominent hepatic steatosis with cytoplasmic vacuoles was observed in HFD and HSD rats.…”
Section: Discussionmentioning
confidence: 56%
“…precise mechanism(s) involved, a vast array of data exists relating to the beneficial impact of probiotics on host health. 102,107,112 However, for the purpose of this review, the focus will be confined to the benefits to infant gut microbiota and subsequent health. With respect to healthy, full term infants, this review has previously outlined the transition that the infant gut undergoes from being initially sterile to having a composition that is relatively stable and resembles that of an adult by 2 years of age.…”
Section: Impact Of Family Structurementioning
confidence: 99%